A CRITICAL DISCOURSE ANALYSIS OF MOHAMAD NASIR’S SPEECH - Ni Putu Santhi Widiastuti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACT Discourse is a unit of language in which its form is longer than a sentence including the vast majority of everyday communication; in addition, it ussually employes specific kinds of language as well as infromation structures to deliver specific purposes. In order to identify the structure and purpose of a discourse, the present research employed Critical Discourse Analysis (CDA) to analyze an educational speech in May 2nd, 2016 delivered by the Indonesian Ministry of Research, Technology, and Higher Education, Mohamad Nasir in the celebration of the National Education Day of Indonesia. The result of the analysis showed how the speech was constructed in form of macrostructure, superstructure, and microstructure revealed how the social power was used by symbolic elites to invite all parties in educational field to join together in reforming educational system of Indonesia to be better than what had been conducted by previous partisans in the past. Keywords: Critical Discourse Analysis (CDA); Indonesian Ministry’s speech; educational speech; National Education Day